ANALISIS SENTIMEN REVIEW DATA TWITTER KOMISI PEMILIHAN UMUM (KPU) MENGGUNAKAN METODE NAÏVE BAYES - Alifvia, Anna Risma; Saprudin, Usep (LPPM Institut Teknologi Bisnis Dan Bahasa Dian Cipta Cendikia, 2023)
Social media is a trend in itself in the daily life of individuals, especially in this country, the survey agency explained its latest data from January 2020, social media users in this country are up to 130 million people with an penetration of 49%. One of them is the KPU's twitter social media which is the process of updating comments on a twitter user in Indonesia. This research is focused on social media twitter in order to review comments about KPU. In solving this research problem, data crawling was carried out to find out negative, positive and neutral responses from the public to the KPU through the social media twitter. To assess an assessment of criticism on all media has problems in the form of analysis on the assessment can be intended. Sentiment analysis in the form of text document classification stages in three classes, namely good, negative and neutral sentiment classes.